Somatosensory evoked potential findings in ankylosing spondylitis. - Cidem, Muharrem; Sahin, Zerrin; Aydin, Teoman; Aysal, Fikret (My University, 2014)
Somatosensory evoked potential (SSEP) abnormalities were reported in patients with ankylosing spondylitis (AS). This study aimed to investigate SSEP abnormalities and its relation with clinical findings in AS patients.

The study included 26 patients with AS and 17 age-matched health volunteers (Control for SSEP). Median nerve SSEP findings were normal in all AS cases.

However, delayed latency and/or very low amplitude of tibial nerve SSEP was found in 20 (76.9%) AS patients. There were significant correlations between tibial SSEP latency and disease duration (R=0.433 to 0.635). There was also an inverse correlation between tibial SSEP amplitude and disease duration (R=-0.429, p=0.047). Serum estradiol level, hip total bone mineral density, The Bath Ankylosing Spondylitis Functional Index (BASFI) score and Beck depression score were significantly lower in AS patients with SSEP abnormalities (37.3±10.8 pg/mL, 0.916±0.123 g/cm(2), 35.0±27.9, 12.8±8.4, respectively) than in AS patients without SSEP abnormalities (53.7±12.3 pg/mL, 1.103±0.197 g/cm(2), 64.8±15.5, 24.8±10.1, respectively).

Significant inverse correlations between SSEP latencies and dehydroepiandrosterone sulphate (DHEAS) levels were found (R=-0.400 to -0.713). There were also significant inverse correlation between SSEP latencies and DHEAS/oestrogen index (R=-0.596 to -0.868), and between SSEP latencies and DHEAS/Progesterone index (R=-0.467 to -0.685). As a conclusion, this study indicates that tibial nerve SSEP abnormalities are common in patients with AS and there are significant correlations between clinical findings of AS and SSEP abnormalities.

Somatosensoriyal uyandırılmış potansiyel (SUP) bozuklukları ankilozan spondilitli (AS) hastalarda bildirilmektedir. Çalışmamızın AS hastalarında amacı SUP anormallikleri ve AS’nin klinik bulguları ile ilişkisini araştırmaktır.

Çalışmada 26 AS’li hasta ve 17 sağlıklı kontrolde SUP yanıtları incelendi. Median sinir SUP bulguları tüm AS olgularında normaldi. Ancak tibial sinirin gecikmiş latansı ve/veya çok düşük amplitüdü AS hastalarının %76,9’unda saptandı.

Tibial SUP latansı ve hastalık süresi arasında anlamlı ilişki vardı (R=0,433–0,635). Tibial SUP amplitüdü ve hastalık süresi arasında da ters bir ilişki vardı (R=−0,429, p=0,047). SUP anormalliği olan AS hastaları, SUP anormalliği olmayan AS hastalarına göre serum östradiol seviyesi, kalça toplam kemik mineral yoğunluğu, Bath Ankilozan Spondilit Fonksiyonel İndeks (BASFI) skoru ve Beck depresyon skoru (sırasıyla 37,3 ± 10,8’ye karşın 53,7±12,3 pg/mL, 0,916±0,123’ye karşın 1,103±0,197 g/cm, 35,0±27,92’ye karşın 64,8±15,5 ve 12,8±8,4’e karşın 24,8±10,1) daha düşüktü.

SUP latansları ve dihidroepiandrosteron sülfat (DHEAS) seviyeleri arasında anlamlı ters ilişki bulundu (R= (−0,400) - (−0,713)). SUP latansları ile DHEAS/östrojen indeksi ve DHEAS/progesterone indeksi arasında anlamlı ters ilişki bulundu (sırasıyla R=(−0,596) - (−0,868) ve R= (−0,467) - (−0,685)). Sonuç olarak AS’li hastalarda tibial SUP bozuklukları sıktır ve AS’nin klinik bulguları ile anlamlı ilişkiler vardır. AS’nin patogenez ve klinik bulguları üzerinde potansiyel nörolojik mekanizmaların etkisini araştıran daha fazla sayıda hasta içeren yeni araştırmalara ihtiyaç vardır.
Keywords: Ankylosing spondylitis; clinical findings; neurologic involvement; somatosensory evoked potentials